2227. Short-Duration of Direct-Acting Antivirals in Hepatitis C Virus-Infected Cancer Patients. (26th November 2018) - Hosry, Jeff; Angelidakis, Georgios; Granwehr, Bruno; Torres, Harrys
Abstract: Background: Short-duration with an 8-week course of ledipasvir/sofosbuvir (LDV/SOF) or glecaprevir/pibrentasvir (GLE/PIB) is considered adequate to treat hepatitis C virus (HCV) infection in selected patients. However, immunocompromised patients with HCV/HIV are not eligible for this approach. Herein, we study the efficacy and safety of an 8-week therapy with direct-acting antivirals (DAAs) in HCV-infected cancer patients. Methods: HCV-infected patients with any type of cancer followed at MD Anderson Cancer Center (June 2014–April 2018) and treated with an 8-week course of LDV/SOF or GLE/PIB were enrolled in a prospective observational study. Efficacy was calculated based on achieving sustained virologic response at 12 weeks (SVR12) after end of treatment per intention to treat (ITT) analysis. A posthoc per-protocol (PP) analysis was done in patients with 12 weeks of follow-up post DAAs. Safety was assessed by emergence of adverse events (AEs) and clinically significant drug–drug interactions (DDIs). Results: Twenty-four patients were treated with a short-duration of DAAs, 22 with LDV/SOF and two with GLE/PIB. General characteristics are described in Table 1. Five patients received concomitant cancer treatment (nivolumab, sorafenib, lenalidomide, tamoxifen and leuprolide), without DDIs noted. Among the patients who have completed DAAs, SVR rates were 87% per ITT (20/23) and 100% PP (20/20) analyses. No patients had grade 2, 3 or 4 AEs. Conclusion: This is the first prospective study to evaluate the use of short-duration of DAAs in HCV-infected cancer patients where these regimens were found to be effective and safe. Disclosures: H. Torres, Gilead Sciences, Merck & Co., Inc.: Grant Investigator, Grant recipient. Vertex Pharmaceuticals: Grant Investigator, Grant recipient.